Behaviour of profiled steel sheet dry board system as walling unit with door opening / Muhammad Zihan Hj. Kisson (Faculty of Civil Engineering, 2003)
Profiled Steel Sheet Dry Board (PSSDB) system is a new structural system in buildings. PSSDB is formed by Profiled Steel Sheet (BONDEK II) and the dry board (CEMBOARD). Between the boarding and the sheeting no adhesive or binder is needed but instead, screws are used to connect them to make the steel sheeting acts compositely with the dry board. The experimental study on the behaviour of PSSDB system with door opening acting as load bearing wall are carried out. PSSDB acts as a membrane carrying the in plane deformation and shear. Three samples with overlap PSS are tested. The size of sample is 1320mm width and 1000mm height. The size of door opening is 300mm width and 700mm height. Flexural failure at the top section of the panel, and overall buckling and crushing (act as column behaviour) on the sides of the panel were observed. The average maximum capacity of the panels is 330KN for overlapped PSSDB system with door opening. Thus, the PSSDB panel could be used as a load bearing wall in housing construction.